2004
DOI: 10.1074/jbc.m400443200
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Microsomal Prostaglandin E2 (PGE2) Synthase-1 Reduces Inducible and Basal PGE2 Production and Alters the Gastric Prostanoid Profile

Abstract: Microsomal prostaglandin E synthase-1 (mPGES-1) is an inducible protein recently shown to be an important source of inflammatory PGE 2 . Here we have used mPGES-1 wild type, heterozygote, and null mice to assess the impact of reduction or absence mPGES-1 protein on the production of PGE 2 and other prostaglandins in lipopolysaccharide (LPS)-treated macrophages and mice. Thioglycollate-elicited peritoneal macrophages with mPGES-1 deficiency were found to lose their ability to produce PGE 2 upon LPS stimulation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
100
2
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(111 citation statements)
references
References 43 publications
8
100
2
1
Order By: Relevance
“…Because PGI 2 and PGE 2 have some redundant functions (8), this increase in PGI 2 generation might act as a compensatory mechanism to ameliorate the physiologic consequences of mPGES1 deficiency. Similar reductions in basal PGE 2 generation with shunting have been reported in other tissue preparations from mPges1 Ϫ/Ϫ mice (41,42). We also found prominent differences in renal prostanoid generation between male and female mice in our studies with basal levels of prostanoid excretion that are almost fourfold higher in female than male mice.…”
Section: Discussionsupporting
confidence: 74%
“…Because PGI 2 and PGE 2 have some redundant functions (8), this increase in PGI 2 generation might act as a compensatory mechanism to ameliorate the physiologic consequences of mPGES1 deficiency. Similar reductions in basal PGE 2 generation with shunting have been reported in other tissue preparations from mPges1 Ϫ/Ϫ mice (41,42). We also found prominent differences in renal prostanoid generation between male and female mice in our studies with basal levels of prostanoid excretion that are almost fourfold higher in female than male mice.…”
Section: Discussionsupporting
confidence: 74%
“…Thus, in the mPGES-1-deficient colon tissues, COX-2-derived prostaglandin H 2 is metabolically shunted into the PGD 2 /PGI 2 -synthetic pathway. In this regard, Boulet et al (2004) have also shown that mPGES-1 deficiency increased the production of PGs other than PGE 2 in the gastric mucosa.…”
Section: Resultsmentioning
confidence: 88%
“…However, Boulet et al [10] studied the shunting of PGH 2 to alternative prostanoid pathways in the presence of complete and incomplete loss of mPGES-1 gene and they did not detect a significant redirection towards TXB 2 in peritoneal macrophages under similar experimental conditions. The reason of these discrepant results is unclear.…”
Section: Page 19 Of 36mentioning
confidence: 99%
“…However, in the stomachs of mice lacking mPGES-1 a shift from PGE 2 to all other prostanoids, i.e. TXA 2 , PGD 2 , PGF 2 , and 5 1 inhibition in the GI tract [10]. Further studies addressing this issue in appropriate animal models are required.…”
Section: Introductionmentioning
confidence: 99%